Peningkatan Kesadaran Keterlambatan Bahasa dan Bicara pada Anak Melalui Penyuluhan di Desa Jaten, Karangnyar - Perdana Putra, Sinar (Politeknik Kesehatan Kemenkes Surakarta, 2024)
Background: Language and speech delay in children is one of the developmental problems often encountered in early childhood. Language and speech are important aspects of child development as they serve as a means of communication, learning and social interaction. According to research, about 5-10% of preschool-aged children experience language and speech delays. These delays can have a long-term impact on children's academic, emotional, and social abilities if not treated properly. Objectives: To increase awareness of language and speech delays in children. Methods: Collaborative approach in the form of counseling and Focus Group Discussion. Results: The p-value of 0.000 indicates that there is a significant difference between pretest and posttest scores. Conclusion: Through increased awareness, it is hoped that the prevalence of language and speech delays can be reduced, so that children have a better chance of achieving their maximum potential, both in academic and social aspects. Keywords: Awareness Raising, Language, Speech, Awareness Raising